Trypanosoma brucei RNA Editing: Coupled Cycles of U Deletion Reveal Processive Activity of the Editing Complex - Alatortsev, Vadim S. (American Society for Microbiology (ASM), 2008)
RNA editing in Trypanosoma brucei is posttranscriptional uridylate removal/addition, generally at vast numbers of pre-mRNA sites, but to date, only single editing cycles have been examined in vitro. We here demonstrate achieving sequential cycles of U deletion in vitro, with editing products confirmed by sequence analysis. Notably, the subsequent editing cycle is much more efficient and occurs far more rapidly than single editing cycles; plus, it has different recognition requirements. This indicates that the editing complex acts in a concerted manner and does not dissociate from the RNA substrate between these cycles. Furthermore, the multicycle substrate exhibits editing that is unexpected from a strictly 3′-to-5′ progression, reminiscent of the unexpected editing that has been shown to occur frequently in T. brucei mRNAs edited in vivo. This unexpected editing is most likely due to alternate mRNA:guide RNA (gRNA) alignment forming a hyphenated anchor; its having only a 2-bp proximal duplex helps explain the prevalence of unexpected editing in vivo. Such unexpected editing was not previously reported in vitro, presumably because the common use of artificially tight mRNA:gRNA base pairing precludes alternate alignments. The multicycle editing and unexpected editing presented in this paper bring in vitro reactions closer to reproducing the in vivo editing process.